Association between hypercholesterolemia and cholesterolosis or vesicular lithiasis - Vilela Desposorio, Carlos David (2020)
Objective: To determine if an association hypercholesterolemia and cholesterolosis or gallbladder lithiasis does exist. Methods: A case series study was conducted between January 2014 and December 2015 in Hospital Belén, Trujillo-Perú. Patients were those in whom a cholecystectomy had been performed (1069) and a lipid profile was available (143). Results: Age range was 17-95 years with a mean age of 50; 36 (25.2%) had cholesterolosis, male to female ratio was 1:2,6 and a mean age of 44,5. Gallbladder lithiasis was found in 119 cases (83.2%), male to female ratio is 1:3.1 and a mean age of 48. Hypercholesterolemia (≥ 200 mg/dl) was found in 51 cases (35.7%); 29 (20,3%) cholesterolosis with gallbladder lithiasis and 7 (4.9%) had acalculous cholesterolosis. No association was found between hypercholesterolemia and cholesterolosis (p=0.284) nor with gallbladder lithiasis (p=0.169). Conclusions: No significant association between hypercholesterolemia and cholesterolosis or gallbladder lithiasis was found.